PENGAWASAN PEMERINTAH KOTA PEKANBARU DALAM MENANGGULANGI PENCEMARAN AIR SUNGAI SIAK TAHUN 2018 (Studi Kawasan Pemukiman Kelurahan Kampung Dalam) - Prowiranata, Rafki; Tinov, M. Y. Tiyas (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
The condition of the Siak River in Pekanbaru City is getting worse due to pollution from household waste and industrial waste. The quality of the Siak River must be considered so that it does not cause harm to water users. The location of the river in the downstream area makes the pollution load experienced by the Siak River even heavier and weak supervision and law enforcement also affects the decline in the quality of Siak River water. This study found that the supervision carried out by the Pekanbaru City Government, in this case the Pekanbaru City Environment and Sanitation Service (DLHK) Against Siak River Pollution in the Settlement Area of Kampung Dalam Village, was considered inadequate, this can be seen from the level of Siak River pollution which is still high enough. The supervisory steps carried out by the Office are as follows: Establishing Supervision Standards, Establishing the Implementation of Supervision Activities, Comparing the Implementation of Supervision Activities, Implementing Corrective Actions against River Pollution. The form of supervision carried out by the government on Siak river pollution in Kampung Dalam Sub-district is in the form of Preventive Supervision, namely in the form of an appeal to the public not to throw garbage into the Siak River stream and Repressive Supervision in the form of imposing sanctions on people who are caught throwing garbage into the Siak River. Obstacles in the implementation of supervision carried out by the Pekanbaru City Environment and Sanitation Service (DLHK) are: 1) Inadequate human resources in both quantity and quality 2) There are no clear regulations to regulate river pollution, especially the Siak River in Pekanbaru City, 3 ) lack of facilities and infrastructure such as a set of tools used to carry out the process of activities to realize the objectives to be achieved, and such as official vehicles, both two-wheeled and four-wheeled, which will be used to go to the field to carry out supervisory activities, it is natural that the activities carried out by the Department of Environment and Sanitation (DLHK) Pekanbaru City is still not being implemented. Keywords: Siak River Pollution Control